1980
DOI: 10.1159/000250480
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo and the HLA System

Abstract: 77 Vitiligo patients were investigated for their HLA phenotype. Analysis of this material according to age of onset and ethnic origin revealed some significant characteristics. Young Jewish Moroccan patients showed a high frequency of B13 when compared to matching controls. Young patients of Yemenite origin had a strikingly high frequency of BW35. Jewish Yemenites showed a lack of B13 both in patients and in controls. It is suggested that studies be undertaken to clarify this problem further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 4 publications
0
34
1
Order By: Relevance
“…The relative risk (RR) for HLA B13 was 9.3 (p = 0. (X)2); for young Yemenites, there was a significant increase in HLA BW35 (R R = 13.89) [13], A study in the Netherlands has reported an increase in HLA A2, DRW6. DRW52 and DQW1 [ 14].…”
Section: Introductionmentioning
confidence: 96%
“…The relative risk (RR) for HLA B13 was 9.3 (p = 0. (X)2); for young Yemenites, there was a significant increase in HLA BW35 (R R = 13.89) [13], A study in the Netherlands has reported an increase in HLA A2, DRW6. DRW52 and DQW1 [ 14].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the study of major histocompatibility complex polymorphism in vitiligo has already shown some promising results [12][13][14][15][16][17][18][19], Reports have documented an increased expression of HLA-DR4 in white [13] and black [15] American patients with vitiligo and HLA-DQw3 in black American vitiligo patients [15]. Metzker et al [16] noted an increased fre quency of HLA-B13 in young Jewish Moroccan and HLABw35 in young Yemenite vitiligo patients, while Poloy et al [18] found an increased presence of HLA-DR 1 in Cau casian Hungarians. To our knowledge, this is the first pub lished report looking at HLA phenotypes, familial inci dence and clinical distribution of vitiligo in the Northern Italian population.…”
Section: Introductionmentioning
confidence: 99%
“…The association of several HLA class I antigens with susceptibility for development of vitiligo has been extensively investigated in the different ethnic population, showing the increased frequencies of the occurrence of HLA-A2, -A30, -A31, -B13, -B46, -Cw4, -Cw6, etc. in patients with vitiligo [1][2][3][4]. On the other hand, by using linkage disequilibrium analysis in familial vitiligo, it has been demonstrated that a major determinant of vitiligo might be located in HLA [5].…”
mentioning
confidence: 99%